Intermittent vs continuous docetaxel therapy in patients with metastatic castration‐resistant prostate cancer – a phase III study (PRINCE). (6th May 2018) - Cash, Hannes; Steiner, Ursula; Heidenreich, Axel; Klotz, Theodor; Albers, Peter; Melchior, Sebastian; Martus, Peter; Fuller, Florian; Magheli, Ahmed; Hinz, Stefan; Kempkensteffen, Carsten; Miller, Kurt; et al.
Abstract : Objective: To investigate non‐inferiority of intermittent docetaxel compared to continuous docetaxel in patients with metastatic castration‐resistant prostate cancer (mCRPC). Patient and Methods: The investigator initiated randomised phase III study included 187 chemotherapy‐naïve patients with mCRPC who were allocated to two treatment arms: intermittent docetaxel and continuous docetaxel. Docetaxel was applied in both arms as weekly (35 mg/m 2 ) or 3‐weekly (75 mg/m 2 ). The primary endpoint was 1‐year survival, which was tested for non‐inferiority (margin δ = 0.125). The secondary endpoints were: overall survival (OS), progression‐free survival (PFS), median time to treatment failure (TTF), and toxicity. Results: Of 156 eligible patients, 78 were allocated to each arm. The intermittent treatment met the non‐inferiority criteria for 1‐year survival (two‐sided 95% confidence interval, −0.12, 18, P = 0.022), but not for OS, according to the result of a post hoc analysis. The differences between the study arms in PFS and TTF were not significant. The median (range) treatment holiday in the intermittent arm was 110 (13–486) days, or 38% of the overall treatment duration. Safety profiles of both study arms were comparable. The main limitation of this study was that the planned number of patients could not be recruited. Conclusion: Intermittent docetaxel chemotherapy was non‐inferior to continuous therapy for 1‐year survival; non‐inferiority in regard to OS was not reached.